Dynamic Evolution of Permeability in Response to Chemo‐Mechanical Compaction. Issue 11 (27th November 2019) - Macente, Alice; Vanorio, Tiziana; Miller, Kevin J.; Fusseis, Florian; Butler, Ian B.
Abstract: Pressure‐solution creep is an important fluid‐mediated deformation mechanism, causing chemo‐mechanical transformations and porosity and permeability changes in rocks. The presence of phyllosilicates, in particular, has previously been hypothesized to further reduce porosity and pore connectivity. Nevertheless, a full characterization of the spatiotemporal evolution of permeability during this process has yet to be reported. A pure NaCl aggregate and a mixture of NaCl and biotite were deformed through pressure‐solution creep while monitoring their microstructural evolution through computed X‐ray microtomography. The evolution of permeability and fluid velocity of the samples were computed by using the pore geometries from the X‐ray microtomography as input for the Lattice‐Boltzmann modeling. The results indicate that, as deformation proceeds, porosity and permeability decrease in both samples. In the salt‐biotite sample pressure solution creep causes the formation of a compaction band perpendicular to the direction of loading, forming a barrier for permeability. Along the other two directions, pore connectivity and permeability are retained in the marginal salt layers, making the sample strongly anisotropic. The presence of biotite controls the way pore coordination number evolves and hence the connectivity of the pathways. Biotite flakes create an enhanced porosity decrease leading to compaction and reduction of pore connectivity. This reduction in porosity affects local stresses and local contact areas, reducing over time the driving force. According to a texture‐porosity process, the reduction in porosity causes salt ions to dissolve in the marginal salt and precipitate within the biotite‐bearing layer, where the bulk volume of salt grains increases over time. Key Points: The presence of biotite prevents permeability along the loading direction and does not affect the permeability of the nearby layers In the absence of biotite, permeability is retained in pore connectivity Pressure‐solution evolves accordingly to a texture‐porosity coupling mechanism